Critical Success Factors Implementasi ERP PT Asuransi Kredit Indonesia - Elke Cahya Putri; Rizal Fathoni Aji (The Indonesian Journal of Computer Science, 2024)
Information technology plays a vital role in achieving corporate objectives, especially for organizations that rely on data integration through technology. Technology-based information systems assist in processing data into high-quality information. To support this, management must maintain the reliability of information, one way being the implementation of Enterprise Resource Planning (ERP). ERP helps enhance the reliability of information for decision-making. This study analyzes the Critical Success Factors (CSFs) in the implementation of ERP at PT Asuransi Kredit Indonesia (PT Askrindo). The primary focus is to identify relevant CSFs to ensure that ERP implementation aligns with the targets of corporate management and the Insurance Holding Company. This supports the shared information technology services initiative toward a single multi-tenant platform within the Insurance Holding environment. The research methods include a case study, literature review, categorization, and qualitative interviews. The results show that PT Askrindo must ensure the success of key factors at various stages of ERP implementation to achieve its goals